Faktor-faktor yang Mempengaruhi Konsumen dalam Keputusan Pembelian Smartphone BlackBerry (Studi Kasus di kota Denpasar) - Yudha, Kusuma (E-Jurnal Manajemen, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Along with the times , telecommunications technology to increase the effectiveness and efficiency of the business but also has become a lucrative business area . The era of telecommunications technology have plagued the joints of human life , where the use of telecommunications technology to help ease the job . several factors such as cultural , personal , social, and psychological participate in decisions affecting consumer purchase of telecommunications equipment , which in this case is the BlackBerry smartphone . there are many things about the behavior of consumers in making purchasing decisions such as , for example, searching for information about items to be purchased , make a purchase , then the post-purchase behavior . Tidah a blackberry smartphone has become a necessity telekomunikasu , but has become a lifestyle trend today . Consumer behavior is influenced by cultural factors , social , personal , and psychological influence consumers in making purchasing decisions blackberry smartphone . Keywords : consumer behavior , purchasing decisions .
Keywords: consumer behavior, purchasing decisions.